SOCIAL-PHILOSOPHICAL BASIS OF WOMEN'S PARTICIPATION IN GOVERNMENT (Universal International Scientific Journal, 2026)
The article studies the participation of women in the public administration system as an object of socio-philosophical analysis. The aspects of the activities of female leaders related to gender equality, social justice, humanism and the development of civil society are revealed. The philosophical foundations of expanding women's participation in public politics in the conditions of new Uzbekistan are scientifically substantiated.
Keywords: public administration, female leaders, gender equality, social justice, social philosophy, New Uzbekistan.